Synthesis and characterization of phosphorylcholine-substituted chitosans soluble in physiological pH conditions - Tiera, Marcio J.; Qiu, Xing-Ping; Bechaouch, Sofiane; Shi, Qin; Fernandes, Julio C.; Winnik, Francoise M. (Amer Chemical Soc, 2006)
A polymer analogous synthesis involving the reductive amination of phosphorylcholine (PC)-glyceraldehyde with primary amines of deacetylated chitosan (M-w approximate to 57000 g mol(-1)) was used to prepare phosphorylcholine-substituted chitosans (PC-CH) with a degree of substitution (DS) ranging from similar to 11 to similar to 53 mol% PC-substituted glucosamine residues. The PC-CH derivatives were characterized by H-1 NMR spectroscopy, FTIR spectroscopy, and multiangle laser light scattering gel permeation chromatography (MALLS-GPC). The pKa of the PC-substituted amine groups (pKa approximate to 7.20) was determined by H-1 NMR titration. The PC-CH samples (1.0 g L-1) were shown to be nontoxic using an MTT assay performed with human KB cells. Aqueous solutions of PC-CH samples (4.0 g L-(1)) of DS g 22 mol% PC-substituted glucosamine residues remained clear, independently of pH (4.0 < pH < 11.0). The remarkable water solubility and nontoxicity displayed by the new PC-CH samples open up new opportunities in the design of chitosan-based biomaterials and nanoparticles.